Presumed reactivation of herpes simplex virus-associated endothelial keratitis after treatment with topical interferon-α 2b for ocular surface squamous neoplasia - Sepehr Feizi; Mohsen Zare; Hamed Esfandiari (BMC Ophthalmology)
Abstract Background To report a case of herpes simplex virus (HSV)-associated endothelial keratitis in a patient receiving topical interferon (IFN)-α 2b for the management of ocular surface squamous neoplasia (OSSN). Case presentation A 65-year-old female was diagnosed with OSSN characterized by gelatinous growth on the left cornea, without conjunctival involvement. She had no history of herpetic keratitis. The patient was treated with topical IFN-α 2b 1 million IU/ml four times daily, leading to complete clinical resolution of the OSSN within three months. However, four months after initiating treatment, while still on the medication, she presented with decreased visual acuity, ocular injection, and pain in the left eye. Slit-lamp examination revealed central corneal stromal edema, infiltration, and keratic precipitates. A diagnosis of HSV endotheliitis was made, and IFN-α 2b was discontinued. The patient was treated with topical betamethasone 0.1% six times daily and oral acyclovir 400 mg five times daily, resulting in complete resolution of the disciform keratitis within three weeks. There has been no recurrence of herpetic infection or OSSN during 10 months of follow-up after discontinuing all medications. Conclusion Ophthalmologists should be alert to the possibility of recurrent herpetic keratitis in patients treated with IFN-α 2b for OSSN who present with sudden visual decline.